Intraspecific sequence and gene expression variation contribute little to venom diversity in sidewinder rattlesnakes (Crotalus cerastes). Issue 1906 (3rd July 2019) - Rautsaw, Rhett M.; Hofmann, Erich P.; Margres, Mark J.; Holding, Matthew L.; Strickland, Jason L.; Mason, Andrew J.; Rokyta, Darin R.; Parkinson, Christopher L.
Abstract : Traits can evolve rapidly through changes in gene expression or protein-coding sequences. However, these forms of genetic variation can be correlated and changes to one can influence the other. As a result, we might expect traits lacking differential expression to preferentially evolve through changes in protein sequences or morphological adaptation. Given the lack of differential expression across the distribution of sidewinder rattlesnakes ( Crotalus cerastes ), we tested this hypothesis by comparing the coding regions of genes expressed in the venom gland transcriptomes and fang morphology. We calculated Tajima's D and F ST across four populations comparing toxin and nontoxin loci. Overall, we found little evidence of directional selection or differentiation between populations, suggesting that changes to protein sequences do not underlie the evolution of sidewinder venom or that toxins are under extremely variant selection pressures. Although low-expression toxins do not have higher sequence divergence between populations, they do have more standing variation on which selection can act. Additionally, we found significant differences in fang length among populations. The lack of differential expression and sequence divergence suggests sidewinders—given their generalist diet, moderate gene flow and environmental variation—are under stabilizing selection which functions to maintain a generalist phenotype. Overall, we demonstrate the importance of examining the relationship between gene expression and protein-coding changes to understand the evolution of complex traits.